Topological Phase Transition and Topological Quantum State Transfer in Periodically Modulated Circuit‐QED Lattice. Issue 9 (5th July 2021) - Cao, Ji; Cui, Wen‐Xue; Yi, Xuexi; Wang, Hong‐Fu
Abstract: The topological properties of a circuit‐QED lattice are studied and it is found that the system undergoes a topological phase transition accompanied by the changes of Chern numbers from 2 to −1. For different lattice sizes, the energy eigenvalue spectra and the probability distributions of edge states are shown. Moreover, it is revealed that, depending on the strictly adiabatic evolution of the time‐dependent Hamiltonian, several different topological quantum state transfers between the first two sites and the last two sites can be achieved by employing the topologically protected edge states as the transfer channels. Further, it is demonstrated that, by using resonator‐based input–output process, the photonic topological edge state can be detected by measuring the average photon number in the steady state. The scheme opens up a new prospect for investigating the potential application of topological matter in quantum information processing. Abstract : The circuit‐QED lattice system undergoes a topological phase transition accompanied by the changes of Chern numbers. Depending on the strictly adiabatic evolution of the time‐dependent Hamiltonian, several different topological quantum state transfers between the first two sites and the last two sites are achieved by employing the topologically protected edge states as the transfer channels.